Role of nerve–muscle interactions and reactive oxygen species in regulation of muscle proteostasis with ageing. (10th September 2017) - Vasilaki, Aphrodite; Richardson, Arlan; Van Remmen, Holly; Brooks, Susan V.; Larkin, Lisa; McArdle, Anne; Jackson, Malcolm J.
Abstract :  Skeletal muscle ageing. Abstract: Skeletal muscle ageing is characterised by atrophy, a deficit in specific force generation, increased susceptibility to injury, and incomplete recovery after severe damage. The hypothesis that increased generation of reactive oxygen species (ROS) in vivo plays a key role in the ageing process has been extensively studied, but remains controversial. Skeletal muscle generates ROS at rest and during exercise. ROS can cause oxidative damage particularly to proteins. Indeed, products of oxidative damage accumulate in skeletal muscle during ageing and the ability of muscle cells to respond to increased ROS becomes defective. The aim of this review is to examine the evidence that ROS manipulation in peripheral nerves and/or muscle modifies mechanisms of proteostasis in skeletal muscle and plays a key role in initiating sarcopenia.